2012
DOI: 10.1016/j.bbamcr.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of Hsp90 in protein complex assembly

Abstract: Hsp90 is a ubiquitous and essential molecular chaperone that plays central roles in many signaling and other cellular pathways. The in vivo and in vitro activity of Hsp90 depends on its association with a wide variety of cochaperones and cofactors, which form large multi-protein complexes involved in folding client proteins. Based on our proteomic work mapping the molecular chaperone interaction networks in yeast, especially that of Hsp90, as well as, on experiments and results presented in the published liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(116 citation statements)
references
References 108 publications
4
104
0
4
Order By: Relevance
“…In addition, these chaperones have been demonstrated to participate in the formation and stabilization of protein complexes (16,17) and have recently emerged as important targets for cancer chemotherapeutics (18,19). To investigate whether the Hsp70/ Hsp90 machinery plays a role in the assembly of the purinosome, we first determined whether these proteins colocalize with In addition, both Hsp70 and Hsp90 were shown to be dynamically associated with the purinosomes as purine levels changed in the media ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, these chaperones have been demonstrated to participate in the formation and stabilization of protein complexes (16,17) and have recently emerged as important targets for cancer chemotherapeutics (18,19). To investigate whether the Hsp70/ Hsp90 machinery plays a role in the assembly of the purinosome, we first determined whether these proteins colocalize with In addition, both Hsp70 and Hsp90 were shown to be dynamically associated with the purinosomes as purine levels changed in the media ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, biogenesis of the 12-subunit Pol II complex remains poorly understood. It was shown previously that Pol II biogenesis requires the R2TP/ Prefoldin-like complex and the ATPase Hsp90 (4), a chaperone Table S1 in the supplemental material for a list of all peptides, Table S2 in the supplemental material for a list of all peptides that interact with Npa3, and that is involved in the assembly of several protein complexes (42), but additional factors are likely involved in Pol II assembly.…”
Section: Discussionmentioning
confidence: 99%
“…hsp90 is a ubiquitously expressed, ATP-dependent chaperone that helps to fold, stabilize, or modify the functions of select client proteins (12,13). We recently found that hsp90 drives heme insertion into sGC during its maturation in cells (14).…”
Section: Soluble Guanylyl Cyclase (Sgc)mentioning
confidence: 99%